Analisis Penggunaan Susu Formula Pada Bayi Usia 0-6 Bulan di Wilayah Kecamatan Ciracas Jakarta Timur - Mera Marhamah; Anes Patria Kumala (NHM PRESS, 2022)
The best food for babies aged 0-6 months is breast milk. Formula milk is only given to babies if there is a medical indication, it must be with a doctor's recommendation regarding the need for a type of formula that is adapted to the baby's condition. Giving formula milk too early can increase the risk of allergies, digestive tract disorders, obesity and others. The purpose of this study was to determine the factors associated with the use of formula milk in infants 0-6 months in the District of Ciracas, East Jakarta. The research design is a quantitative analytic study with a Cross Sectional approach. The sample in this study were mothers who had babies aged 0-6 months totaling 52 people. Sampling using Accidental Sampling technique. Data were analyzed using Chi square test. The instrument used is a questionnaire that has been tested for validity and reliability. The results showed that of the 52 respondents 31 (59.6%), mothers used infant formula, 29 (55.8%) had poor knowledge, 36 (69.2%) had negative attitudes, 34 (65.4%) had less husband support, 34 (65.4%) and 33 (63.5%) mothers were affected by the promotion of formula milk. The results of the chi square analysis showed that there was a significant relationship between knowledge, attitude, husband's support, and promotion of formula milk with the use of formula milk in infants. The conclusion of the study was that the most influential factor on the use of formula milk in infants 0-6 months was knowledge (OR = 64.125).